Ammonite fauna from the Wenonah Formation (Upper Cretaceous) of New Jersey - Kennedy, W; Cobban, W (1994)
The Wenonah Formation of New Jersey yields an ammonite fauna comprising Menuites portlocki (Sharpe, 1855), Placenticeras placenta (DeKay, 1828), P. minor n. sp., Nostoceras (Nostoceras) puzosiforme n. sp., Nostoceras (Nostoceras) aff. N. colubriformis Stephenson, 1941, Didymoceras n. sp., Didymoceras spp., Parasolenoceras sp., Baculites cf. B. scotti Cobban, 1958, Baculites sp., and Trachyscaphites pulcherrimus (Roemer, 1841). The presence of M. portlocki and T. pulcherrimus is an indicator of upper, but not uppermost, Campanian in the northwest European sense, and the presence of Baculites cf. B. scotti suggests uppermost middle Campanian in terms of the Western Interior provincial substages. -Authors